Assessment of Relapse in Patients with Peritoneal Carcinomatosis after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy using F-18-FDG-PET/CT - Klumpp, B.; Schwenzer, N. F.; Gatidis, S.; Koenigsrainer, I.; Koenigsrainer, A.; Beckert, S.; Mueller, M.; Claussen, C. D.; Pfannenberg, C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: In patients with peritoneal carcinomatosis (PC), cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is an evolving therapeutic approach with curative intention. The differentiation between posttherapeutic findings after HIPEC and relapse of PC is challenging. We evaluated the diagnostic value of F-18-FDG-PET/CT in patients with relapse of PC after HIPEC.Materials and Methods: 36 patients with recurring PC after HIPEC were examined on a whole-body PET/CT system (44 examinations). The examination included 3 D F-18-FDG-PET and contrast-enhanced CT. Images were assessed by two experienced readers regarding the presence and the extent of PC using the peritoneal carcinomatosis index (PCI). Imaging results were correlated with surgical findings or follow-up.Results: Relapse was suspected in 40 of 44 examinations. Relapse was missed by F-18-FDG PET/CT in 4 patients and significantly underestimated in 8 patients. The diagnostic accuracy for the detection of PC on a patient basis was 91 %, the sensitivity was 91 % and the positive predictive value was 100 %. The mean PCI was 11.4 ± 11.9 for PET/CT, 8.4 ± 10.3 for CT and 16.6 ± 15.0 in the case of surgical exploration. The extent of PC was underestimated by PET/CT and even more by CT alone (p < 0.05).Conclusion: The diagnostic value of F-18-FDG PET/CT after cytoreductive surgery and HIPEC in the detection of recurring PC is superior to contrast-enhanced CT. However, the quantification of the extent of PC is limited due to post-therapeutic tissue alterations.Key Points:• Imaging of recurrent PC after HIPEC is challenging due to posttherapeutic tissue alterations.• The extent of recurrent PC after HIPEC is systematically underestimated by F-18-FDG PET/CT.• F-18-FDG PET/CT provides improved sensitivity for recurrent PC compared to contrast-enhanced CT.• The correlation of the extent of recurrent PC depicted by F-18-FDG PET/CT and surgical exploration is better than that of contrast-enhanced CT and surgical exploration.Citation Format:• Klumpp B, Schwenzer N F, Gatidis S et al. Assessment of Relapse in Patients with Peritoneal Carcinomatosis after Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy using F-18-FDG-PET/CT. Fortschr Röntgenstr 2014; 186: 359 – 366
Keywords: PET/CT; peritoneal carcinomatosis; relapse; HIPEC; cytoreductive surgery